REVIEW SISTEMATIS PENGARUH SUDUT PULLEY PRIMER DAN RASIO GEARBOX PADA MOTOR MATIK - Riski Kurniawan; Donny Fernandez; Irma Yulia Basri; Iffarial Nanda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The Continuously Variable Transmission (CVT) largely determines the performance of automatic motorcycles, with the primary pulley angle and the gearbox (final-drive) ratio being the two most frequently modified components. This study systematically reviews research on the effect of modifying the primary pulley angle and gearbox ratio on speed, fuel consumption, and exhaust emissions of automatic motorcycles. Following the PRISMA protocol, articles were retrieved from Google Scholar, Garuda, SINTA, and DOAJ; of 248 identified records, 16 met the inclusion criteria. Bibliometric analysis shows a rising publication trend during 2021–2025, dominated by nationally accredited (SINTA) journals not yet indexed in Scopus. The synthesis indicates that reducing the pulley angle from 14° to 13.5°–13.8° tends to increase V-belt clamping force, torque, and power, whereas reducing the gearbox ratio raises top speed but lowers wheel torque (a trade-off). Fuel consumption and emissions (CO and HC) are strongly governed by the shift of the engine operating point (RPM). The review reveals a gap: few studies isolate each component’s effect or measure speed, fuel, and emissions simultaneously at identical RPM points.Keywords: CVT, primary pulley angle, gearbox ratio, fuel consumption, exhaust emissions.